Wittgenstein on the human spirit - Lurie, Yuval (Value inquiry book series, 2012)
Provides a new understanding of Wittgenstein's discourse as an edifying philosophy of culture, pursued through self-reflection. Investigates the conceptual underpinnings of culture, revealing them as shared expressive spiritual forms of life.